Adoption of Smart Contracts in the Philippine Government Construction Industry - Verde, Leslie Ashlyn; Ganiron, Tomas U. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Poor payment practices continue to plague not only the private construction industry but also the government construction sector. According to recent studies, conditions and instructions can be encoded into smart contracts to allow automatic payments. The construction industry in the Philippines is slow to adapt to new technologies. This research proposes the adoption of smart contracts for implementing Philippine government infrastructure projects. By analyzing datasets from the Cordillera Administrative Region, this study determined the willingness of government employees and contractors to adopt smart contracts for government projects and identified factors causing doubt among contractors and government employees about its implementation. A total of 218 professionals responded to a Google Form questionnaire, and 20 participants were involved in unstructured interviews, which supported the data and results from the questionnaire. To interpret and validate the data gathered, a two-tailed t-test analysis was used. The study revealed that the Philippine government construction industry, specifically in the CAR region, is not yet ready to adopt smart contracts. It was also found that smart contracts will only be effective with proper introduction through seminars and training.